Strategic Technology Foresight in Organizations through Quality Management and Business Excellence Concepts: A Case Study - Aichouni, Mohamed; Touahmia, Mabrouk; Alghamdi, Abdulaziz S; Kolsi, Lioua; Al-Homaid, Tarik (Edelweiss Applied Science and Technology, 2020)
We are living in an era of accelerated change and uncertainties where disruption in all aspects of our modern lives is the norm. In such context, foresight supported by quality management systems and organizational excellence frameworks comes into prominence as strategic toolset to face these social and economic challenges in organizations and societies and ensure sustainability. Foresight has been widely used by organizations as a strategy to support leadership and decision makers in situations that involve big uncertainties towards the future. The present paper is a conceptual study in the sense it discusses the relationship between organization`s foresight capability and quality management and organization excellence approaches. Essentially, we will attempt to answer the fundamental research question: “To what extent quality management and organizational excellence approaches and models lead to enabling and building future foresight capability of modern organizations?” For that purpose, a survey questionnaire was developed based on literature review, and administered online to leadership of Saudi organizations national wide. Statistical analysis performed. The analysis showed that quality management and organization excellence frameworks implementation in Saudi organizations would be an enabler for successful foresight implementation. This led to pronounce that in order to achieve their strategic objectives in line with the national vision 2030, Saudi organizations should implement quality management systems such as ISO 9001:2015 and the national quality award (KAQA). It is believed that the paper opens a discussion between quality professionals and foresight experts on the potential link between quality management principals and foresight capability in modern organizations operating in an accelerated change environment and disruption.